Recurrent scleral patch graft shrinkage and Ahmed valve tube exposure - Mansoori, Tarannum (Nepalese Journal of Ophthalmology, 2019)
Aim: To report a case of recurrent Ahmed glaucoma valve (AGV) tube exposure dueto scleral patch graft (SPG) melt Background: AGV is a useful modality in the management of medically refractory glaucoma. Human donor SPG has been employed to cover the external portion of the tube to prevent its exposure. Case Description : A 23 year old male with Anterior chamber intraocular lens (ACIOL)had undergone retinal detachment (RD) surgery with silicone oil insertion (SOI)followed by SO removal (SOR), re- RD and SO re-injection, followed by implantation of Ahmed glaucoma valve (AGV) for uncontrolled glaucoma in the right eye. Three months after the AGV implantation, he presented with exposure of the subconjuctival portion of AGV tube with melted, displaced and shrunk donor sclera graft, which was managed by placing larger sized, full thickness, donor scleral patch graft (SPG) over the exposed tube. Six months later, he presented again with tube exposure and the donor SPG was found to be retracted nasally and shrunk to one fourth of its original size. The AC portion of the tube was blocked by the SO bubble and the emulsified SO could be seen inside the exposed tube. The patient underwent SOR with tube explanation and intraocular pressure was later controlled with transscleral cyclophotocoagulation and medical management. Conclusion : SPG thinning and the overlying conjunctival erosion can occur after the AGV implantation. This can cause AGV tube exposure and hence, long - term patient follow up is essential to ensure timely identification of this possible complication and prompt treatment.